Fabrication of periodical Ag–Au compound nanostructure films with controllable Ag nanoparticle aggregate patterns: a study on surface‐enhanced Raman scattering. (26th June 2015) - Ruan, Weidong; Cui, Yinqiu; Lin, Feng; Zhou, Tieli; Hui, Ge; Wang, Ye; Chen, Yufeng; Lu, Fei; Guo, Jie; Zhao, Bing
Abstract : The Ag–Au compound nanostructure films with controllable patterns of Ag nanoparticle (NP) aggregates were fabricated. A strategy of two‐step synthesis was employed toward the target products. Firstly, the precursor Au NP (17 nm) films were synthesized as templates. Secondly, the Ag NPs (45 nm) were deposited on the precursor films. Three types of Ag NP aggregates were obtained including discrete Ag NPs (discrete type), necklace‐like Ag NP aggregates (necklace type), and huddle‐like Ag NP aggregates (huddle type). The surface‐enhanced Raman scattering (SERS) property was studied on these nanostructures by using the probing molecule of rhodamine 6G under the excitation laser of 514.5 nm. Interestingly, the different types of samples showed different enhancement abilities. A statistical method was employed to assess the enhancement. The relative enhancement factor for each Ag NP was estimated quantitatively under the ratio of 1 : 25 : 18 for the discrete‐type, necklace‐type, and huddle‐type samples at the given concentration of 10 −8 mol/l. This research shows that the enhancement ability of each Ag NP is dependent on the aggregate morphology. Moreover, the different enhancement abilities displayed different limit detection concentrations up to 10 −8, 10 −11, and 10 −9 mol/l, separately. The understanding of the relationship between the defined nanostructures and the SERS enhancement is very meaningful for the design of new SERS substrates with better performance. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Three kinds of Ag–Au compound nanostructures with controllable Ag nanoparticle aggregate patterns were fabricated with or without the help of polystyrene microsphere monolayer templates. The surface‐enhanced Raman scattering (SERS) property was studied on the obtained Ag nanoparticle aggregates. Interestingly, the different types of substrates showed different SERS enhancement abilities at an enhancement factor ratio of 1 : 25 : 18. The results are very meaningful for designing SERS substrates with high performance.